Natural vs. synthetic repellents on treated clothing: advantages, challenges and their efficacy - Mohd Darwis, Rabiatul Adawiyah; Che Ros, Fadhlina; Osman, Nurul Huda; Abdul Halim, Norhana (Penerbit Universiti Teknologi Malaysia, 2023)
Arthropod-borne viruses have become a major threat to human health worldwide. The implementation of personal protection through clothing is necessary to avoid insect bites, especially for military operations and public health emergencies. Development of synthetic repellents in clothing impregnation has been well-established whilst, numerous studies regarding the application of essential oils on textile substrates have been carried out to develop their use as an alternative to synthetic repellents. The present review attempts to give a general overview and summarize the current technology used in treated clothing, as well as the advantages, challenges, limitations, and factors that may affect the performance of synthetic repellents and essential oils in textiles. Current research trends in developing more effective repellents from essential oils are also summarized.